HARMONI LINTAS AGAMA DI MEDIA MASSA - Mohammad Ali Hisyam (Millah: Journal of Religious Studies, 2009)
The article is intended  to elaborate the problems of dialogue among  religions in  mass media  discourse that  is occurred in  Indonesia within  last few  years. At  the end, it  tries to offer  alternative  solutions that  may  be suitable  with  the problem. The analysis indicates that  mass media  has a strategic role to support the dialogue. However, the role should  be followed  by the  awareness of  the mass media to be consistent and  commited  to maintaining the harmony  among  religions. The mass media should not  change its objective.